Classifying Written Corrective Feedback for Research and Educational Purposes: A Typology Proposal - Benjamín Cárcamo (Universidad Nacional de Colombia, 2020)
Although several investigations have been carried out in recent years on written corrective feedback (WCF), there is a lack of agreement about its definition and the effect on students' writings of different types of feedback. This may be due to the lack of systematicity regarding the characterization of WCF used in those studies. This article seeks to review the concept of WCF in studies in the field and to systematize the various aspects considered in a typology, which includes specification, focus, scope, source, mode of delivery, and notes. The resulting typology should help improve the effectiveness in the comparison of WCF studies and serve as a reference for teachers interested in expanding their practices.